Synthesis and Growth Promoting Effect of Chlorosubstituted 4-Aroylpyrazolines on Some Vegetable Crops - G. Potdar, Shashank; D. Bhoyar, Amol; Parhate, V.V.; Maurya, M.R.; Rajput, P.R. (Asian Journal of Chemistry, 2010)
In the present study, the synthesis and growth promoting effect of 4-aroylpyrazolines on vegetable crops, namely, cluster bean, alibanam, lady's finger and sorrel were undertaken.